Pemberdayaan Remaja Putri Melek Pangan Lokal Sumber Zat Besi dalam Pencegahan Anemia di SMAN 13 Kota Jambi - Nurita, Suci Rahmani; Perwitasari, Tuhu; Nurfitriani, Nurfitriani (Jurnal Abdimas Kesehatan (JAK), 2024)
Young women are a group of people who are vulnerable to the problem of malnutrition in their daily food consumption. Iron deficiency is the most common cause of anemia. The prevalence of anemia among adolescents in the world ranges from 40-88%, of which 22.2% of anemia sufferers in Indonesia are aged ≥ 15 years. Handling anemia with food ingredients is still rarely done even though it has such great potential to prevent anemia, especially in young women. The purpose of implementing this educational activity is to increase knowledge. This activity was carried out from March to August 2023 which began with identification of partner problems, educational activities for young women and Hb checks for adolescents who felt symptoms of anemia. Materials are given through lectures, demonstrations and discussions with participants. Evaluation of the knowledge of young women before education is assessed by conducting a pretest, then given education once for 45-60 minutes. After the education ended, another evaluation was carried out in the form of a posttest with the same questions as the pretest. This activity was attended by 17 students of class XII IPS 1 SMAN 13 Jambi City. The results of the evaluation during the educational process were that the participants seemed enthusiastic about the counseling material, the participants listened to the counseling carefully and the participants asked questions related to the material that was not clear. The results of the pre-test and post-test showed an increase in participants' knowledge from before the activity and after the educational activity by 1-3 points. Screening results were obtained from 17 female students, it was identified that 1 person had anemia with an Hb level of 10.6 g%. Scientific publications in the form of articles submitted to the journal Abdimas STIKes Baiturrahim Jambi and HKI outputs in the form of copyright booklets Prevent Anemia with Blood Supplement Tablets and Anti-Anemia Local Food Consumption in Young Women have been registered..